1982
DOI: 10.1073/pnas.79.4.1129
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative model for gene regulation by lambda phage repressor.

Abstract: A statistical thermodynamic model has been developed In prokaryotes, genes are commonly switched on and off by the interactions of regulatory proteins with specific DNA sequences. A particularly complex example of such a switch is found at the right operator (OR) ofbacteriophage A: this operator consists of three tandem DNA sites that are recognized by two phage-encoded regulatory proteins (the A repressor and cro protein). When phage A is in the "lysogenic state," the A repressor (cI gene product) is synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
615
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 576 publications
(630 citation statements)
references
References 23 publications
12
615
0
3
Order By: Relevance
“…3, we will assume that p1 activates G1 and G2; p2, which is the gene product of G1 acts as a repressor of G2. Based on these assumptions, the following rate laws were derived using the method proposed by Shea-Ackers (Ackers et al 1982) for transcriptional binding kinetics.…”
Section: Modelingmentioning
confidence: 99%
“…3, we will assume that p1 activates G1 and G2; p2, which is the gene product of G1 acts as a repressor of G2. Based on these assumptions, the following rate laws were derived using the method proposed by Shea-Ackers (Ackers et al 1982) for transcriptional binding kinetics.…”
Section: Modelingmentioning
confidence: 99%
“…The pioneering studies of Jacob, Monod, Ptashne and Gilbert explained how these two processes, seeming inverses of each other, while being maintained in local chemical equilibrium, could still lead to robust genetic switches by coupling to protein synthesis and degradation which are kinetically controlled far from equilibrium processes (1)(2)(3)(4). This classic picture, with the law of mass action at its core (5,6), suggests that understanding the molecular mechanism of the binding and release of transcription factors is of secondary interest compared with understanding the thermodynamics of protein-DNA recognition. The recent discovery of protein induced release of a DN A-bound transcription factor in the N F κB/IκB/DN A genetic switch changes this picture (7).…”
mentioning
confidence: 99%
“…Binding to oR2 stimulates expression of CI itself from the relatively weak pRM. Early work concentrated on the oR region where the promoter for CI and a number of lytic genes are located (Ackers et al 1982). Meticulous studies of binding affinities revealed subtle differences in affinity as well as cooperative effects that were important for the regulatory switch (Burz et al 1994).…”
Section: Introductionmentioning
confidence: 99%